Repeated liver stiffness measurement compared with paired liver biopsy in patients with non-alcoholic fatty liver disease - Kamarajah, Sivesh Kathir; Chan, Wah Kheong; Nik Mustapha, Nik Raihan; Mahadeva, Sanjiv (Springer Verlag, 2018)
Introduction: The value of repeated liver stiffness measurement (LSM) in non-alcoholic fatty liver disease (NAFLD) has not been shown before. Methods: A longitudinal study of biopsy-proven NAFLD patients was conducted at the Asian tertiary hospital from November 2012 to January 2017. Patients with paired liver biopsies and LSM were followed prospectively for liver-related and non-liver related complications, and survival. Results: The data for 113 biopsy-proven NAFLD patients (mean age 51.3 ± 10.6 years, male 50%) were analyzed. At baseline, advanced fibrosis based on histology and LSM was observed in 22 and 46%, respectively. Paired liver biopsy and LSM at 1-year interval was available in 71 and 80% of patients, respectively. High-risk cases (defined as patients with advanced fibrosis at baseline who had no fibrosis improvement, and patients who developed advanced fibrosis on repeat assessment) were seen in 23 and 53% of patients, based on paired liver biopsy and LSM, respectively. Type 2 diabetes mellitus was independently associated with high-risk cases. The median follow-up was 37 months with a total follow-up of 328 person-years. High-risk cases based on paired liver biopsy had significantly higher rates of liver-related complications (p = 0.002) but no difference in other outcomes. High-risk patients based on paired LSM had a significantly higher rate of liver-related complications (p = 0.046), cardiovascular events (p = 0.025) and composite outcomes (p = 0.006). Conclusion: Repeat LSM can predict liver-related complications, similar to paired liver biopsy, and may be useful in identifying patients who may be at an increased risk of cardiovascular events. Further studies in a larger cohort and with a longer follow-up should be carried out to confirm these observations.